2014
DOI: 10.1016/j.ymgme.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in the SLC25A15 gene in a Turkish patient with HHH syndrome: Functional analysis of the mutant protein

Abstract: The hyperornithinemia–hyperammonemia–homocitrullinuria syndrome is a rare autosomal recessive disorder caused by the functional deficiency of the mitochondrial ornithine transporter 1 (ORC1). ORC1 is encoded by the SLC25A15 gene and catalyzes the transport of cytosolic ornithine into mitochondria in exchange for citrulline. Although the age of onset and the severity of the symptoms vary widely, the disease usually manifests in early infancy. The typical clinical features include protein intolerance, lethargy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…However, normal brain CT scan or MRI findings were reported in several patients, mainly in those who did not experience an overt hyperammonemic coma [36,40,60]. Interestingly, multiple stroke-like lesions were reported in a 4 year-old patient presenting irritability, vomiting, highly elevated liver enzymes, hyperammonemia, and coagulopathy [56].…”
Section: Resultsmentioning
confidence: 99%
“…However, normal brain CT scan or MRI findings were reported in several patients, mainly in those who did not experience an overt hyperammonemic coma [36,40,60]. Interestingly, multiple stroke-like lesions were reported in a 4 year-old patient presenting irritability, vomiting, highly elevated liver enzymes, hyperammonemia, and coagulopathy [56].…”
Section: Resultsmentioning
confidence: 99%
“…Control cultures with the empty vector were processed in parallel. Inclusion bodies were purified on sucrose density gradient and washed at 4°C, first with TE buffer (10 mM Tris/HCl, 1 mM EDTA, pH 8), then twice with a buffer containing Triton X-114 (2% w/v) and 10 mM HEPES, pH 8, and, finally, with HEPES 10 mM, pH 7.5 (48). Proteins were solubilized in 2% (w/v) Sarkosyl and purified by centrifugation and Ni 2ϩ -nitrilotriacetic acid-agarose affinity chromatography, as described previously (49).…”
Section: Methodsmentioning
confidence: 99%
“…Among the 38 different mutations found to cause HHH syndrome, the most common are p.Phe188del and p.Arg179*, which are found in 45% of the patients. The effects of many disease-causing mutations on ORC1-catalyzed transport have been assessed in reconstituted liposomes by the EPRA method and by in vitro cell culture studies, which have shown that, with very few exceptions, the mutations are deleterious for activity [111,[115][116][117]. Some of the mutations (p.Glu180Lys, p.Arg275Gly and p.Arg275Gln at positions 183 and 279) ( Figure 2B,D) are in the contact points (Figure 1), changing residues that were proved experimentally to participate directly in substrate binding [31].…”
Section: Slc25a15 (Ornithine Carrier 1 Orc1) Deficiencymentioning
confidence: 99%